Investigating Structural Property Relationships to Enable Repurposing of Pharmaceuticals as Zinc Ionophores - Oisín Kavanagh; Robert Elmes; Finbarr O'Sullivan; John Farragher; Shane Robinson; Gavin Walker (MDPI AG, 2021)
The importance of zinc in biology has gained greater recognition in recent years due to its essential contributions to the function of many endogenous enzymes. Disruption of zinc homeostasis may be useful in treating pathological conditions, such as Alzheimer's, and for antiviral purposes. Despite the growth of knowledge and increased interest in zinc, little is known about the structure and function of zinc ionophores. In this study we analyse the Cambridge Structural Database and solution complexation studies found in the literature to identify key functional groups which may confer zinc ionophorism. Pharmaceuticals, nutraceuticals and amino acids with these functionalities were selected to enable us to explore the translatability of ionophoric activity from in vitro assays to cellular systems. We find that although certain species may complex to zinc in the solid and solution states, and may carry ions across simple membrane systems, this does not necessarily translate into ionophoric activity. We propose that the CSD can help refine key functionalities but that ionophoric activity must be confirmed in cellular systems.